HUBUNGAN GAYA KEPEMIMPINAN KEPALA RUANG RAWAT YANG DIPERSEPSIKAN OLEH PERAWAT PELAKSANA TERHADAP KEPUASAN KERJA PERAWAT PELAKSANA DI RUMAH SAKIT - Yohan Wenas Gunawan; Setyowati; Andreasta Meliala (Journal of Health Service Management, 2016)
Background: Nurses are the biggest health personnel in thehospital. Despite their important role in providing services topatients, their job satisfaction is still low. Leadership is one of thefactors affecting the nurses’ job satisfaction. Objective: The research was conducted to measure therelationship between head nurse leadership style and nurses’job satisfaction in hospital wards. Methods: This study was an analytic research using crosssectionaldesign. This research was conducted in the DistrictHospital on May 2015. Subjects were 156 nurses who work inthe general and special wards. Questionnaire was divided into 3sections, demography variable, job satisfaction using Mueller-McCloskey Satisfaction Scale and leadership style using“Multiple Leadership Questionnaire 5x”. Results: Marital status, educational level, and type of wardhave a significant relationship with job satisfaction with p valueof 0,033, 0,010, and 0,007 respectively. Transformationalleadership style also has a significant relationship to jobsatisfaction, providing four times greater job satisfactioncompared to passive avoidant style (p = 0,01). Conclusion: There is a relationship between head nurse’leadership style and nurse job satisfaction. Hospitalmanagement has to give serious attention on nursingleadership to enhance attending nurses’ job satisfaction.